The challenge of progress : theory between critique and ideology - Dahms, Harry F. (Current perspectives in social theory, 2019)
Globalization has accelerated the process of social, political, cultural, and especially economic transformations since the 1990s. In recent decades, this has cast doubt over the validity and reliability of many working assumptions about the nature and logic of progress in modern societies, at all levels of social structure and complexity. In The Challenge of Progress, editor Harry F. Dahms and a series of contributors explore how this doubt has been magnified, looking at how the institutions and constellations between business, labor and government have begun to weaken. The essays included in this volume examine the foundations, nature and contradictions of progress in the modern era. Anchored by - but not exclusively focused on - a debate of Amy Allen's recent book, The End of Progress: Decolonizing the Normative Foundations of Critical Theory (2016), the eleven essays identify, analyse and confront the challenges of progress, looking across social class, philosophy, history and culture in their analyses. For researchers and students across social theory, this is an unmissable volume confronting the present and future of our societies. Examining the choices of modern society, Dahms and contributors ask: what are the social costs of "progress"?